Analysis Of Factors Associated With Utilisation Of Health Services In Inpatients UPT. RSUD Kuala Kurun - Perdias, Antonio; Noor, Zairin; Istiqomah, Ermina; Kania, Nia; Tri Febriana, Silvia Kristanti (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari Banjarmasin, 2025)
Utilisation of health services at UPT. RSUD Kuala Kurun in the last two years has decreased. Factors that influence the utilisation of health services include education level, accessibility, and facilities. To determine the relationship between education level, accessibility, and facilities with the utilisation of health services among inpatients at the Kuala Kurun Regional Hospital. This study used a cross sectional design. The research subjects consisted of 105 people at UPT Kuala Kurun Hospital. Data analysis chi square test and multiple logistic regression test. The results showed that the most dominant variables related to the utilisation of health services in inpatients of UPT. RSUD Kuala Kurun were accessibility (13,022), education level (6,690), and facilities (3,638). There is a relationship between the level of education, accessibility and facilities to the utilisation of health services in inpatients UPT. RSUD Kuala Kurun. The most dominant variable is accessibility.